Operation and Control of Grid Connected Hybrid AC/DC Microgrid using various RES - Kodanda Ram R B P U S B; Venu Gopala Rao Mannam (Institute of Advanced Engineering and Science, 2014)
This paper proposes a Hybrid AC/DC Microgrid in alliance with Photo Voltaic (PV) energy, Wind Energy and Proton Exchange Membrane (PEM) Fuel cells. Microgrids are becoming increasingly attractive to the researchers because of the less greenhouse gases, low running cost, and flexibility to operate in connection with utility grid. The Hybrid AC/DC Microgrid constitutes independent AC and DC subgrids, where all the corresponding sources and loads are connected to their respective buses and these buses are interfaced using an interfacing converter. The Hybrid AC/DC Microgrid increases system efficiency by reducing the multiple reverse conversions involved in conventional RES integration to grid. A Small Hybrid AC/DC Microgrid in grid connected mode was modeled and simulated in MATLAB-SIMULINK environment. The simulation results proves the stable operation considering the uncertainty of generations and loads.DOI: http://dx.doi.org/10.11591/ijpeds.v5i2.6188